2017
DOI: 10.1111/mmi.13762
|View full text |Cite
|
Sign up to set email alerts
|

ALBA4 modulates its stage‐specific interactions and specific mRNA fates during Plasmodium yoelii growth and transmission

Abstract: Summary Transmission of the malaria parasite occurs in an unpredictable moment, when a mosquito takes a blood meal. Plasmodium has therefore evolved strategies to prepare for transmission, including translationally repressing and protecting mRNAs needed to establish the infection. However, mechanisms underlying these critical controls are not well understood, including whether Plasmodium changes its translationally repressive complexes and mRNA targets in different stages. Efforts to understand this have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 64 publications
6
78
0
Order By: Relevance
“…For instance, in both P. yoelii and P. falciparum , CelTOS, GEST and SPELD were not detected or were only weakly expressed in oocyst sporozoites, but were among the most abundant proteins in salivary gland sporozoites (Table 2, Table S1). Moreover, the presence/absence of cellular regulators such as specific ApiAP2s, histone modifiers, RNA-binding proteins and other proteins (Table S1) agree with previous reports describing how these types of regulation may be used by the sporozoite 32, 40, 48 .…”
Section: Resultssupporting
confidence: 90%
“…For instance, in both P. yoelii and P. falciparum , CelTOS, GEST and SPELD were not detected or were only weakly expressed in oocyst sporozoites, but were among the most abundant proteins in salivary gland sporozoites (Table 2, Table S1). Moreover, the presence/absence of cellular regulators such as specific ApiAP2s, histone modifiers, RNA-binding proteins and other proteins (Table S1) agree with previous reports describing how these types of regulation may be used by the sporozoite 32, 40, 48 .…”
Section: Resultssupporting
confidence: 90%
“…As our recent RNA-sequencing data from Plasmodium yoelii shows that all four genes are expressed in asexual blood stages and in gametocytes (4), we sought to determine if any of the CCR4 domain-containing proteins played an important, stage-specific role in the parasite life cycle. To this end, we replaced their coding sequences with a GFP-expression cassette and a human dihydrofolate reductase (HsDHFR)-expression cassette via double homologous recombination in the Plasmodium yoelii 17XNL strain (Figures S2CDEF).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that the parasite requires tight transcriptional and translational control to navigate these complex transmission events (48). Despite the complex events required for the effective transmission of the parasite, Plasmodium has only one known, expanded family of specific transcription factors, the ApiAP2 proteins (reviewed in (9)).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the abundant presence RNA-binding proteins [13, 14] and RNA degradation components [15] in the P. falciparum genome. The includePfALBA1 [16], PfCAF1 [17] in P. falciparum and PyCCR4 [18], PyALBA4 [19] in rodent-specific P.yoelii all of which functions were directly implicated in regulation of transcript levels. Moreover, variability of mRNA half-lives across the IDC observed by several experimental approaches also suggested a significant contribution of mRNA decay in regulation of gene expression in malaria parasites [20].…”
Section: Introductionmentioning
confidence: 99%